Art, Liturgy and the Transformation of Memory: Christian Rapprochement with Buddhism in Post-Independence Sri Lanka. (11th January 2017) - Harris, Elizabeth
Abstract : In the middle of the twentieth century, a group of Sri Lankan Christians, from a diversity of churches, sought rapprochement with Buddhism, in the context of long-standing Buddhist mistrust of Christianity, conditioned by memory of the colonial period. They included Yohan Devananda, Vijaya Vidyasagara, Michael Rodrigo omi, and Aloysius Pieris sj. One face of this wish for rapprochement found expression in the performative. Devananda devised a 'New World Liturgy' for his Christian ashram that included Buddhist readings. Vidyasagara, through the Christian Workers Fellowship (CWF), helped create a Workers' Mass that used Buddhist terminology to highlight elements within Christianity. Rodrigo, who was murdered in 1987 whilst he was living in an entirely Buddhist village, expressed what he had learned from the Buddhists of this village in poetry and participated in Buddhist rituals and festivals. Pieris, at his research and dialogue centre, Tulana, invited Buddhist artists to interpret Christian themes through art. This article examines these examples against the backdrop of Buddhist mistrust of Christianity stemming from Sri Lanka's colonial past and explores the extent to which the expression of respect by Christians through the performative has transformed memory of the colonial period.